Feasibility of Offering Bachelor of Technical Vocational Teacher Educa-tion (BTVTEd) Major in Computer Hardware Servicing in Sorsogon State University – Bulan Campus - Medalla, Jopet Vincent B.; Dipad, Mark Anthony D.; Bongalosa, Corazon G. (Future Science / FSH-PH Publications, 2021)
Based on CHEd Memorandum Order No. 79, series of 2017, the Bachelor of Technical Vocational Teacher Education (BTVTEd) Major in Computer Hardware Servicing program is designed to enhance the knowledge, desirable values and skills of computer service technicians in accordance with industry standards. This mixed design research sought to determine the feasibility of offering this program in Sorsogon State University - Bulan Campus (SorSU-BC). It was found that the offering of the program is highly necessary and can expect a moderate sufficiency of enrolees. The program will also provide significant benefits to the different domains of the society such as the government, the community, the business industries and the students. The offering of the program is also highly sustainable in terms of enrolment, faculty, competition and facilities. It is also consistent with the vision and mission of the university and adheres to the pertinent legal foundations. Generally, faculty requirements are complied with but there is a need to hire faculty members with master’s degree in technology education or its equivalent. The laboratories and physical facilities required for the offering of the program are already available considering the existence of the IT-education and teacher-education programs. Therefore, the offering of BTVTEd major in Computer Hardware Servicing is found to be feasible. It is recommended for SorSU Bulan Campus to craft a program curriculum for BTVTEd Computer Hardware Servicing so that it can be offered in the university with the approval of the Commission on Higher Education.